แนวการปฏิบัติและแนวโน้มทางการบัญชีการเงิน และการเปิดเผยข้อมูลเกี่ยวกับสิ่งแวดล้อมของอุตสาหกรรมประเภทที่มีผลกระทบโดยตรงหรือมีนัยสำคัญต่อสิ่งแวดล้อม - จักรพันธ์ จินดาวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purpose of this thesis is to study the practices and trend of environmental financial accounting and environmental information disclosure between 1996 to 2001. The sample included 40 corporations from the 9 industries identified by the United Nations to have direct or significant environmental impacts. Content analysis was done on their financial reports and environmental performance reports. The statistical significance test of change is McNemar Test. In-depth interviews on environmental accounting practices were conducted with 7 financial controllers selected from the sample corporations. The hypothesis testing results indicate increases of environmental accounting and environmental information disclosure in the years 1996 and 2001 at the significant level of 0.05. Qualitative disclosure was the type used by most corporations while the other two types include quantitative and financial. The interviewees mentioned problems in measuring and classifying environment related transactions because of lacking accounting standard on the environmental issue. In addition, the results also reveal that national economic condition was the most important external factor impacting disclosure format. The most important internal factors were management attitude and policy on the environmental management. The increases in disclosures found in this research were driven by the ISO 14000 certificate the corporation received and voluntariness to report environmental performances.